OPTIMALISASI KOMUNIKASI PELAYANAN PUBLIK DALAM MENINGKATKAN KEPUASAN PELANGGAN MELALUI APLIKASI TRANS JATIM AJAIB - Fitriawardhani, Tira; Ekantoro, Julyanto; Kenanga, Nur Fitri Ani (Publicio: Jurnal Ilmiah Politik, Kebijakan dan Sosial, 2024)
Optimizing public service communication to enhance customer satisfaction through the Trans Jatim Ajaib Application is an important step in providing optimal service to the public. By leveraging digital technology and responsive features to user needs, this application can facilitate access to information, ticket booking, and interaction between customers and service providers. Through research focused on improving customer satisfaction, the government can gain valuable insights to design more effective and responsive service strategies, thereby enhancing overall service quality and user experience. The researchers employed a qualitative research method with a descriptive approach. With this approach, the research aimed to identify the extent to which this application meets the established standards of public service communication and to determine customer satisfaction regarding public services delivered through the mobile application using interview, observation, and documentation methods. The research findings indicate that the implementation of communication through the Trans Jatim Ajaib Application has proven successful in delivering public service information and enhancing customer satisfaction. Users acknowledge that the application provides ease of access, convenience, and beneficial features that meet their needs. Although there are notes and expectations for improvement regarding technical issues, overall, user satisfaction and communication levels regarding this application are high.